Strategies for Private-Sector Development and Civil-Service Reform in the Kurdistan Region-Iraq - Hansen, Michael L. (RAND Corporation, 2014)
This monograph provides strategies to reemploy civil-service workers in the private sector and to increase private-sector employment in the Kurdistan Region-Iraq. The research is based on a variety of methods, including analyses of survey data, analysis of Kurdistan regional and Iraqi national documents and laws, and a qualitative assessment of numerous conversations with government officials and private-sector employers.